Preliminares Enletawa Journal 11.1 - Romero Archila, Yuranny Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Enletawa Journal is an academic publication of the Masters in Language Teaching at Universidad Pedagógica y Tecnológica de Colombia. The Journal provides a means of dissemination of academic research, pedagogical innovation, and theoretical discussion articles. Enletawa Journal is a biannual publication that receives articles in English, French and/or Spanish. For comments, contributions or journal exchanges please write to Maestría en Docencia de Idiomas, UPTC Avenida Central del Norte 39 - 115 Edificio Central, office C-224; PBX: (+57) 8 7405626 Ext. 2470. http://revista.uptc.edu.co/revista/revistas/index.php/ enletawa_journal1%20